Eumops floridanus (Chiroptera: Molossidae). (30th September 2021) - Vannatta, Jessica M; Gore, Jeffery A; Mathis, Verity L; Carver, Brian D
Abstract: Eumops floridanus (Allen, 1932) is a molossid commonly called the Florida bonneted bat or the Florida mastiff bat. Eumops floridanus is the largest species of bat in Florida and is one of 16 species in the genus Eumops . With one of the smallest distributions of any bat in the United States, it is endemic to southern peninsular Florida where it roosts in cavities of live and dead trees and man-made structures. Eumops floridanus was formerly classified as a subspecies of E. glaucinus but has been elevated to species level based on morphology. Due primarily to its restricted distribution, small population size, and the continued loss of habitat, E. floridanus is federally listed as "Endangered" (EN) by the United States Fish and Wildlife Service.